Analyzing time-different connectedness among systemic financial markets during the financial crisis and conventional era: New evidence from the VARX-DCC-MEGARCH model - Xiaoxing Liu; Khurram Shehzad (Journal of Applied Economics, 2023)
This investigation utilized the VARX-DCC-MEGARCH model assimilated with skewed-t density to analyze the time-different (i.e., daytime, overnight, and daily) connectedness among S&P 500, DAX 30, FTSE-100, Nikkei 225, and Shanghai Composite Index. This investigation discovered that the current daytime returns transmission from the DAX 30, FTSE 100, and Nikkei 225 index to ensuing overnight returns of the S&P 500 index was inconsequential during the stable period. The study also quantified that shocks befallen in the current overnight returns of the S&P 500 partake bidirectional and negative ties with shocks that occurred in subsequent day-wise returns of the DAX 30 index. Moreover, during crises, only the Shanghai composite index spillovers the volatility of the FTSE 100 index. The study revealed a leverage effect for the day-wise return of the S&P 500, DAX 30, and overnight returns of the FTSE 100 index.
Keywords: 330; Financial crisis; Leverage effect; Returns transmission; Time-varying correlations; Volatility spillover effect